Potentials of sawmill wood wastes for pulp and paper production (2008)
This study was carried out to assess the suitability of sawnil1 wood wastes as potential raw material for the production of pulp and paper in Nigeria. Sawmill wastes of three wood species: Aningeria robusta, Nesogordonia papaverifera and Terminalia ivorensis were selected for the study. There were three set factors: control, shaving and saw dusts. The collected wood samples were macerated using a solution of glacial acetic acid and hydrogen peroxide. Data collected were analysed using a combination of descriptive and anova. The result showed that the average fibre length of the species for the control ranged between 1.1321mm, 1.0660mm and 1.5040mm for Aningeria robusta, Nesogordonia papaverifera and Terminalia ivorensis respectively. The fibre lengths of wood shaving are 1.0978mm, 1.0361mm and 1.2888mm for Aningeria robusta, Nesogordonia papaverifera and Terminalia ivorensis respectively while the fibre lengths of the sawdust are 1.0391mm, 0.8694mm and 1.1495mm respectively. Average fibres lengths of untreated wood of the studies species compare favorably with those of Gmelina arborea and fourteen Nigerian Savanna species. Average fibres lengths of untreated wood of the studies species compare favorably with those of Gmelina arborea and fourteen Nigeria Savanna species. It was however discovered that the effect of machining of wood on the fibre length is significant. Sawdust and shavings should be explored for paper production in Nigeria. Research should be carried out to establish the pulping characteristics of sawdust and shavings and the paper grades for which they are best suited. Research should also reveal the form the degree of modification like blending with long fibre pulp that should be incorporated into the materials in order to perfect them for the desired use(s).